Desinfestação e estabelecimento de sementes de Myrciaria dubia (H.B.K.) McVaugh germinadas in vitro - Silva, Marcela Liege da (2012)
The camu-camu is a fruit which possesses a high content of ascorbic acid and has been standing out in the production of concentrates and natural supplements. Due to that importance, the domestication of the camu-camu has been being studied for some years. Among the different propagation processes, the in vitro cultivation has been important in the process of cloning of selected materials. However, there is not yet successful works which make the in vitro establishment of the species viable and provide the multiplication of selected materials and/or production of high quality seedlings. In this context, it was intended through the present work to develop procedures for both the disinfestation and in vitro establishment from camu-camu seeds. For the disinfestations, the application of fungicide and formol; the use of fungicide and sodium hypochlorite and the effect of concentrations of sodium hypochlorite and immersion time of the seeds were evaluated. For the in vitro cultivation of camu-camu seeds, the inoculation in different culture media and sucrose concentrations and different concentrations of the MS medium and sucrose were tested. It was found that use of fungicide combined with formol and hypochlorite was efficient in disinfestation of camu-camu seeds, the best results were obtained when the seeds were immersed for 3 hours in fungicide followed for 3 hours’ immersion in formol and afterwards for 25 minutes in hypochlorite. Use of fungicide for 6 hours and next of hypochlorite for 25 minutes, without the addition of formol, also can be utilized in the asepsis of camu-camu seeds. The utilization of sodium hypochlorite for disinfestation of camu-camu seeds at the concentration of 0.5 to 1% of active chlorine for 20 and 60 minutes proved efficient. The products utilized in the disinfestation of the seeds were not harmful to the germination of the seeds evaluated. The addition of sucrose into the culture media MS, WPM and BOXUS did not result into the initial growth of camu-camu in vitro.